Quality monitoring of intellectual and developmental disabilities systems in the US: Assessing the utility and applicability of selected National Core Indicators to national and state priorities - Bradley, Valerie; Hiersteiner, Dorothy (Frontiers in Rehabilitation Sciences, 2022)
Abstract: This article provides historical context on evolution of performance measures for system improvement, examines the perspectives and insights of state public managers on the use and utility of NQF-endorsed outcome measures from the NCI®-IDD In-Person Survey (IPS) for quality improvement, and discusses the necessity of ensuring that outcome measures align with policy goals.